Apical extrusion of debris with root canal instrumentation in primary teeth: A systematic review - Drishti Kaushal; Srinivas Gosla Reddy; Krishna Prasad Biswas; Ashutosh Dixit; Rebecca Chowdhry; Ashi Chug (Wolters Kluwer Medknow Publications, 2022)
Aim: This study aimed to systematically review available literature of in vitro studies on apical extrusion of debris through rotary instrumentation in comparison to manual instrumentation in pediatric endodontics, and also to perform a comparison between various rotary instrumentation systems for assessment of debris extrusion. Materials and Methods: A comprehensive search was conducted on PubMed, Medline, Cochrane Library, Embase, Scopus, and Google Scholar without any language restriction and year of publication. A planned search strategy was made for PubMed and applied to other databases. After full-text reading, 7 articles were selected for quantitative synthesis. Modified CONSORT checklist of items for reporting in vitro studies of dental materials was used for quality assessment of included studies. Results: Root canal preparation with rotary instrumentation led to lesser apical debris extrusion than manual instrumentation. Self-adjusting file system was associated with the least debris extrusion among all included studies, followed by ProTaper Next, Kedo-S, ProTaper, K3, Mtwo, Revo-S, and Wave One. Conclusion: More apical debris extrusion was seen with manual instrumentation than rotary instrumentation. Furtrhermore, variance in debris extrusion was seen with different rotary file systems.